mu-Adipato-kappa O-2(1):O-4-bis{[2,6-bis(1H-benzimidazol-2-yl-kappa N-3)pyridine-kappa N](nitrato-kappa O)lead(II)} - Wei, L.Q.; Zeng, M.H.; Ng, S.W. (International Union of Crystallography, 2010)
The dinuclear title compound, [Pb-2(C6H8O4)(NO3)(2)(C19H13N5)(2)], lies with the mid-point of the butyl chain of the bridging adipate unit on a center of inversion. The Pb-II ion is covalently bonded to the nitrate anion and is bonded to a carboxylate group of the adipate unit by another covalent bond. The N-heterocycle functions in a chelating tridentate mode. The metal atom exists in a Psi-octahedral coordination environment. When weaker Pb center dot center dot center dot O interactions are also considered, the geometry is a Psi-tricapped trigonal prism in which the lone-pair electrons occupy one face of the trigonal prism. Adjacent molecules are linked into a layer structure by N-H center dot center dot center dot O hydrogen bonds.